The Analysis of Persona in Suzanna Collin's “The Hunger Games” Movie - Pretty Yuliastika Putri Siregar; Gaguk Rudianto (Institut Agama Islam Negeri Palopo, 2022)
In real life as a mirror life, literature is the one things that happen in the life of human beings and their surrounding. As a careful student , who discuses literary works is an effort to be able to add experience about life and to gain knowledge about human life itself by using all kinds of problems. The movie discusses in this article by title The analysis of persona in Suzanna Collin’s “The Hunger Games” Movie. This article will be analyzed by using Carl Gustav Jung’s archetypes theory to make a comparative study through of the novel. This study concern of the Jung’s archetypes of the persona. The method of the researcher took is descriptive text analysis. The article also used the comparative study. The results of this study can show the different an achievements of persona by presenting of the characters of the Suzanna Collin’s in the analysis of persona. This article concern to C. Guctav Jung’s theory that discusses about the persona. The method of the research is descriptive analysis. This article can show the different of persona through representation of the character of Katniss Everdeen in The Hunger Games.